Angiotensin-Converting Enzyme Genotype–Specific Immune Response Contributes to the Susceptibility of COVID-19: A Nested Case–Control Study - Gong, Pengyun; Mei, Fanghua; Li, Ruili; Wang, Yuchen; Li, Weizheng; Pan, Kai; Xu, Junqiang; Liu, Chao; Li, Hongjun; Cai, Kun; Shi, Wei (Frontiers in Pharmacology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of coronavirus disease (COVID-19), which has resulted in a global pandemic. In this study, we found that the Angiotensin-converting enzyme (ACE) deletion polymorphism was associated with the susceptibility to COVID-19 in a risk-dependent manner among the Chinese population. Moreover, genotype-specific cytokine storms and immune responses were found enriched in patients with ACE deletion polymorphism, suggesting the contribution of the susceptibility to COVID-19. Finally, we identified the immune pathway such as complement system related to the ACE protein expression of patients by lung and plasma proteomics. Our results demonstrated that it is very important to consider the gene polymorphisms in the population to discover a host-based COVID-19 vaccine and drug design for preventive and precision medicine.